Quantitative shotgun proteomics distinguishes wound-healing biomarker signatures in common carp skin mucus in response to Ichthyophthirius multifiliis - Mona Saleh (Veterinary Research, 2018)
Abstract Ichthyophthirius multifiliis is a ciliated protozoan parasite recognized as one of the most pathogenic diseases of wild and cultured freshwater fish. Fish skin mucus plays a significant role against invading pathogens. However, the protein-based modulation against infection with I. multifiliis, of host fish at this barrier is unknown. Thus, we investigated the skin mucus proteome of common carp using a shotgun proteomic approach at days 1 and 9 after I. multifiliis exposure. We identified 25 differentially expressed proteins in infected carp skin mucus. Upregulated proteins were mainly involved in metabolism, whereas downregulated proteins were mainly structural. This is the first proteomic analysis of infected common carp skin mucus, and it provides novel information about proteome alteration caused by I. multifiliis. Furthermore, we identified novel proteins with yet unknown function in common carp following penetrating injuries such as olfactomedin 4, lumican, dermatopontin, papilin and I cytoskeletal 18. This analysis, therefore, represents a key for the search for potential biomarkers, which can help in a better understanding and monitoring of interactions between carp and I. multifiliis. This proteomic study not only provides information on the protein-level pathways involved in fish-ciliate interactions but also could represent a complementary system for studying tissue repair.